A bluetooth-based wireless distributed data acquisition and control system - Afonso, José A. (2006)
This paper presents an application independent embedded platform for a wireless distributed data acquisition and control system, and describes its application in the scenario of controlling the information processing and communications between sensors and actuators onboard of an autonomous flying robot, in a “fly-by-wireless” approach. The system, which was designed and implemented, comprises a set of nodes composed by microcontrollers, wireless communication modules based on Bluetooth technology, and sensing/actuation devices. This paper also presents several experimental results which denote encouraging performance characteristics for the developed system, not only in the context of the proposed application, but for other wireless applications as well.